2021
DOI: 10.1159/000515435
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transfer and Fetal Pharmacodynamics of Sildenafil in the Pregnant Sheep Model

Abstract: <b><i>Background:</i></b> Sildenafil is a phosphodiesterase-5 inhibitor considered for antenatal use for a variety of indications. We sought to assess sildenafil pharmacokinetics in the pregnant ewe and fetus and evaluate its physiological fetal effects. <b><i>Methods:</i></b> Twelve fetal lambs (127–133 days GA, term 145) were chronically catheterized in utero. Ewes received different doses of sildenafil, either via subcutaneous injection (1.6, 2.0 mg/kg/day) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Fetal mean arterial pressure and HR were not different during the basal and SC MRI acquisition windows. Given that SC can transiently alter fetal blood pressure [25], we began MRI acquisitions 15 min after the onset of fetal SC exposure in an attempt to avoid any potential transient haemodynamic instability. Unlike recent findings by De Bie et al [25], we found no impact of SC on blood pressure, transient or otherwise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fetal mean arterial pressure and HR were not different during the basal and SC MRI acquisition windows. Given that SC can transiently alter fetal blood pressure [25], we began MRI acquisitions 15 min after the onset of fetal SC exposure in an attempt to avoid any potential transient haemodynamic instability. Unlike recent findings by De Bie et al [25], we found no impact of SC on blood pressure, transient or otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Given that SC can transiently alter fetal blood pressure [25], we began MRI acquisitions 15 min after the onset of fetal SC exposure in an attempt to avoid any potential transient haemodynamic instability. Unlike recent findings by De Bie et al [25], we found no impact of SC on blood pressure, transient or otherwise. It should be noted that fetal SC exposure during the STRIDER trials occurred over a chronic timeframe and thus acute transient alterations to fetal blood pressure or HR at the onset of SC exposure are unlikely to impact longer-term cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the two sheep studies in this field have both demonstrated effects of sildenafil at fetal concentrations well below the currently used therapeutic range. Both an acute pulmonary vasodilatory effect ( de Bie et al, 2021b ) and an effect on neonatal cardiopulmonary hemodynamics (suggesting a longer-term effect on pulmonary vascular development) ( Kashyap et al, 2019 ) were observed at concentrations that are currently assumed to be ‘subtherapeutic’. It is therefore possible that the required fetal sildenafil concentration to achieve the desired developmental effect is lower than the concentration required to achieve acute vasodilation in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In a fetal lamb model with CDH, prenatal sildenafil exposure reduced pulmonary arterial pressure and increased pulmonary blood flow after birth, resulting in improved gas exchange [ 113 ]. However, the transplacental transfer of sildenafil to the fetal compartment in sheep was later shown to be very minimal [ 114 ]. This is tied to this animal model.…”
Section: Congenital Diaphragmatic Herniamentioning
confidence: 99%